2019
DOI: 10.22543/7674.62.p319326
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the factors affecting the motivation for learning from the perspective of public health students: A qualitative study

Abstract: Objective. Despite the significant role of motivation in achieving success among public health students, students often do not demonstrate adequate motivation for learning and education. This study was performed to determine factors affecting the motivation for learning from the perspective of public health students via content analysis approach. Methods. This qualitative study was conducted at Kurdistan University of Medical Sciences in Sanandaj, Iran in 2017. 15 students were included in the study by using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
0
0
1
Order By: Relevance
“…The findings showed that students indicated that the support from the university in alleviating their challenges through academic and financial policies was crucial in enhancing their motivation to learn in addition to the psychological and scholar support from their advisors and professors. This is consistent with Allahqoli et al (2019) which have found that university policy that eased the educational process was a key factor in mediating the motivation of nursing students. This is also supported by Tharani et al (2017) which have also conducted a qualitative analysis on the motivation of nursing students and have found that the rules and regulations set by the university has had significant impact on the motivation of the students, where more considerate policies has shown to enhance the motivation and academic achievement.…”
Section: Discussionsupporting
confidence: 91%
“…The findings showed that students indicated that the support from the university in alleviating their challenges through academic and financial policies was crucial in enhancing their motivation to learn in addition to the psychological and scholar support from their advisors and professors. This is consistent with Allahqoli et al (2019) which have found that university policy that eased the educational process was a key factor in mediating the motivation of nursing students. This is also supported by Tharani et al (2017) which have also conducted a qualitative analysis on the motivation of nursing students and have found that the rules and regulations set by the university has had significant impact on the motivation of the students, where more considerate policies has shown to enhance the motivation and academic achievement.…”
Section: Discussionsupporting
confidence: 91%
“…Ngoài ra, thông qua việc tạo môi trường học tập thuận lợi, thiết lập mục tiêu học tập rõ ràng cùng với sự nhiệt tình trong bài giảng có thể giúp sinh viên tìm thấy niềm vui và hứng thú trong học tập [6]. Bên cạnh đó, sự hỗ trợ của gia đình, trường đại học và chính quyền, cũng như việc lập kế hoạch học tập của sinh viên không chỉ thúc đẩy sức khỏe tâm lý mà còn đóng một vai trò quan trọng trong việc học tập của sinh viên [7].…”
Section: Giới Thiệuunclassified